The comparison of the efficacy and safety of q-switched potassium titanyl phosphate laser and long-pulsed neodymium-doped yttrium aluminum garnet laser in the treatment of erythematotelangiectatic and papulopustular rosacea - Üstüner, Pelin; Balevi, Ali; Özdemir, Mustafa (Galenos Yayıncılık, 2018)
Objective: The best laser for patients with erythematotelangiectatic rosacea is still a controversial topic. The efficacy and safety of Q-switched potassium titanyl phosphate (KTP) and long-pulsed neodymium-doped yttrium aluminum garnet (lpNd:YAG) lasers were compared in the treatment of erythematotelangiectatic and papulopustular rosacea. Methods: Thirty patients aged 16-70 years who had multiple telangiectasias on both sides of the face and a diagnosis of stage 1-2 rosacea were included in a split-face, double-blinded, randomized clinical trial. Lasers were applied to two different sides of the face for four sessions at one-month intervals. The number of papules and pustules were investigated before treatment and at each visit. The erythematotelangiectatic rosacea severity scores, thickness of telangiectasias, clinician's assessment of treatment response, patient satisfaction, and adverse effects were examined. Results: In the third and fourth months, the number of papules on the side treated with lpNd: YAG laser was significantly lower than the other side. In the fourth month, the mild or severe erythematotelangiectatic rosacea score rate was significantly lower on the side treated with lpNd: YAG laser. The clinician's assessment was similar for both treatments. Conclusion: We recommend lpNd: YAG laser for erythema and Q-switched KTP laser for thin and superficial telangiectasias for the highest treatment efficacy.

Amaç: Eritemotelenjiektatik rozasealı hastalar için en iyi lazer halen tartışmalı bir konudur. Q-anahtarlı potassium titanyl phosphate (KTP) ve uzun atımlı neodymium-doped yttrium aluminum garnet (lpNd:YAG) lazerlerin eritemotelenjiektatik ve papülopüstüler rozasea tedavisinde etkinliği ve güvenilirliği karşılaştırıldı. Yöntemler: Yüzünün her iki yanında çok sayıda telenjiektazileri olan ve evre 1-2 rozasea tanısı bulunan 16-70 yaşları arasında 30 hasta yarım-yüz, çift-kör, randomize klinik çalışmaya alındı. Lazerler yüzün iki farklı yanına bir aylık aralıklarla 4 seans uygulandı. Tedavi öncesinde ve her takipte papül ve püstül sayısı araştırıldı. Eritemotelenjiektatik rozasea şiddet skoru, telenjiektazi kalınlığı, klinisyenin tedavi yanıtını değerlendirmesi, hasta memnuniyeti ve yan etkiler incelendi. Bulgular: Üçüncü ve dördüncü aylarda, lpNd:YAG lazer ile tedavi edilen taraftaki papüllerin sayısı diğer tarafa oranla anlamlı oranda daha düşük idi. Dördüncü ayda hafif veya şiddetli eritemotelenjiektatik rozasea skor oranı lpNd:YAG lazer ile tedavi edilen tarafta anlamlı oranda daha düşük idi. Klinisyenin değerlendirmeleri her iki tedavi için benzer idi. Sonuç: En yüksek tedavi etkinliği için eritemde lpNd:YAG lazeri, ince ve yüzeyel telenjiektazilerde Q-anahtarlı KTP lazeri önermekteyiz.
Eritemotelenjiektatik ve papülopüstüler rozasea tedavisinde q-anahtarlı potassium titanyl phosphate lazer ve uzun atımlı neodymiumdoped yttrium aluminum garnet lazerin etkinliği ve güvenilirliğinin karşılaştırması
WOS: 000437821200004
Keywords: Erythema; Lasers; Purpura; Rosacea; solid-state; Telangiectasias; Eritem; Lazerler; Purpura; Rozasea; Katı Hal; Telenjiektaziler